The Effect of Educational Intervention on Improvement of Breastfeeding Self-Efficacy: A Systematic Review and Meta-Analysis - Azam Maleki; Elham Faghihzadeh; Samaneh Youseflu (Obstetrics and Gynecology International)
Background. Self-efficacy is an important psychological and motivational factor in breastfeeding, and it is a valuable framework that predicts breastfeeding outcomes and demonstrates maternal confidence in breastfeeding. The meta-analysis evaluated the effectiveness of educational interventions on improving breastfeeding self-efficacy (BSE). Methods. The English and Persian databases including Medline, Embase, Cochrane Database of Systematic Reviews (CDSR), PubMed, Web of Science, Scopus, CINAHL, Sid, IRANDOC, and Marg-Iran were systematically searched for studies published from January 2005 to December 2020. The quality of studies was evaluated using the Cochrane risk of bias tool and the heterogeneity by I2 statistic. The extracted data were analyzed using RevMan 5 statistical software and presented using random effects standardized mean difference (SMD). The funnel plot was used for evaluating publication bias. Results. Results from 40 RCTs showed that educational intervention had a positive effect on the BSE compared with the usual/standard care (pooled SMD = 1.20; 95% CI = 0.75–1.64, p value <0.001). The subgroup analysis indicated that the educational intervention was based on theory, group class format, direct method education, during the first week of postpartum, doing during pregnancy, on primiparous women, and health center setting, and the Asian region has a more effect on BSE than the others. Conclusion. Breastfeeding education is considered an influential factor in the improvement of BSE. It is recommended that breastfeeding education should be continued for several weeks after childbirth for gaining its benefit. The Asian region has a more effect on BSE than the others. Therefore, it is important to add the values in content of education in each country.